2000
DOI: 10.1038/sj.bmt.1702639
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome after conversion to FK 506 (tacrolimus) therapy for acute graft-versus-host disease resistant to cyclosporine or for cyclosporine-associated toxicities

Abstract: Summary:This retrospective study describes the outcome in 53 patients who had immunosuppressive treatment changed from cyclosporine (CSP) to tacrolimus for resistant acute GVHD (n = 23), hemolytic uremic syndrome (HUS) (n = 13) or CSP-associated neurotoxicity (n = 17). Tacrolimus was administered at doses of 0.03 mg/kg/day intravenously or 0.12 mg/kg/day orally in divided doses, as tolerated. Median time of conversion to tacrolimus after transplant was day 47. Nineteen patients had treatment changed to tacroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 41 publications
(26 reference statements)
0
29
0
3
Order By: Relevance
“…18 Although blood levels of cyclosporine and tacrolimus tend not to correlate with PRES, medication withdrawal often results in alleviation of toxicity. 33,34 The cause of neurotoxicity with PRES remains controversial. From a historical persective, hypertension with failed autoregulation and hyperperfusion has been suggested as the cause of the developing vasogenic edema.…”
Section: Discussionmentioning
confidence: 99%
“…18 Although blood levels of cyclosporine and tacrolimus tend not to correlate with PRES, medication withdrawal often results in alleviation of toxicity. 33,34 The cause of neurotoxicity with PRES remains controversial. From a historical persective, hypertension with failed autoregulation and hyperperfusion has been suggested as the cause of the developing vasogenic edema.…”
Section: Discussionmentioning
confidence: 99%
“…A switch from cyclosporine to tacrolimus in our hands was useful only in patients in whom the switch occurred because of neurotoxicity. 60 Phototherapy pursues a different strategy. Based on initial observations in patients with cutaneous T-cell lymphoma or various dermatologic disorders, 8-methoxypsoralen is given to patients orally before external exposure to ultraviolet irradiation in the UVA range (320-400 nm) to sensitize circulating T lymphocytes to UV energy.…”
Section: Primary Therapy and Its Impactmentioning
confidence: 99%
“…44,45 Switching from CsA to FK506 proved to be beneficial for 12% of patients. 46 ATG was another option for steroid-resistant patients. Unfortunately, a prospective randomized Group for Marrow Transplantation study showed no difference between patients who were randomized to receive 2 mg/kg of 6MPD for 10 days alone and those who were administered 6MPD associated with rabbit ATG.…”
Section: Second-line Treatmentmentioning
confidence: 99%